Hubungan antara Stres Kerja dengan Symptom Depresi - Sari, Nining Gilang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between work stress and depressive symptoms in employees at the Meranti Islands District Attorney's Office. This research method uses descriptive analysis with a cross-sectional approach. The results of the study showed that employees at the Pulau Meranti Prosecutor's Office experienced the most job stress with no qualifications, namely 17 people (64%), and the most depressive symptoms with standard qualifications were 17 people (68%) and there was a significant relationship between job stress. Depressive symptoms in employees at the Meranti Islands District Prosecutor's Office which was characterized by a significant p-value of 0.045 < 0.05. In conclusion, there is an essential relationship between work stress and depressive symptoms in employees at the Meranti Islands District Attorney's Office. Keywords: Employees, Depression Symptoms, Work Stress